Hubungan Antara Kecerdasan Emosional dan Perkembangan Sosial Terhadap Kedisiplinan Siswa Kelas X di SMK Negeri 1 Banjarbaru - Sella Ananda Pristiya Dwi Hartati; Husnul Madihah; Aminah Aminah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Student discipline is an important aspect of character development and educational success, particularly in vocational high schools where students are expected to demonstrate responsibility, self-control, and readiness for social and professional environments. Discipline is not only influenced by school rules but also by students’ emotional and social capacities. Emotional intelligence enables students to recognize, regulate, and manage emotions, while social development supports their ability to interact, adapt, and build positive relationships with others. This study aimed to examine the relationship between emotional intelligence and social development with student discipline among tenth-grade students at SMK Negeri 1 Banjarbaru. A quantitative approach with a descriptive correlational design was employed. The participants consisted of 189 tenth-grade students selected using purposive sampling. Data were collected using Likert-scale questionnaires measuring emotional intelligence, social development, and student discipline. The data were analyzed using multiple linear regression with SPSS version 25 after the assumptions of normality and linearity were fulfilled. The results showed that emotional intelligence and social development had a significant simultaneous relationship with student discipline, as indicated by an F value of 39.407 and a significance value of p < 0.05. Partially, emotional intelligence had a significant relationship with student discipline, with a t value of 5.342 and p < 0.05. Social development also had a significant relationship with student discipline, with a t value of 4.074 and p < 0.05. The coefficient of determination showed that emotional intelligence and social development contributed 58.6% to student discipline, while the remaining 41.4% was influenced by other factors outside this study. These findings indicate that students with higher emotional intelligence and better social development tend to demonstrate stronger discipline in school. This study provides practical implications for teachers, school counselors, and parents in strengthening students’ emotional and social competencies as part of character education and discipline-building programs.